ANALISIS KELAYAKAN INVESTASI ARMADA PADA PT BUMI JASA UTAMA KALLATRANSPORT TAHUN 2013-2015 - Astuty Hasti; Daryanti Daryanti (AkMen JURNAL ILMIAH, 2019)
This research aims to find out the company's plan to increase the investment in assets in the form of an additional fleet, from this research it can be seen whether the addition of the fleet can be said to be feasible or not to be carried out. Investment made by PT. Bumi Jasa Utama related to the investment feasibility analysis of the addition of the fleet can be said to be feasible. The appraisal of investment worthiness is seen from the financial aspects of the company, which in the investment appraisal uses four calculation methods namely Payback Period (PP) where capital returns are faster ie 4 years 2 months 5 days than the economic age of the fleet which is 8 years so that investment with this method is feasible to be implemented, the Net Present Value (NPV) obtained a value of Rp 2,189,446,661, or greater than 0 so that it can be said to be feasible because it provides benefits over the life of the investment, the Internal Rate of Return (IRR) method I can say is feasible because in the calculation of the value of the IRR that I get which is 12.42% in other words the investment made by the company is greater than the expected rate of return of 10% and the Profitability Index (PI) of this method I can say is feasible because of the calculation between the net cash flow and the value investments get a return of 1.07 in other words PI on investment conducted by companies greater than 1.